Using of Open-Graded Bituminous Mixtures in Iraq (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Open graded mixtures or porous asphalt mixture (PAM) is mainly implemented on surface drainage layer on the pavements of the high-speed trafficked highways because it has many application  advantages such as : noise reduction and  safety throughout the rainfalls, as a result of its open structure, the water is stored and horizontally moved inside the layer, reducing the effects of the splash and spray, thereby increasing the drivers’ visibility throughout the rainfalls. Alternatively, the main drawback of the porous asphalt layers are the low stiffness, high rutting and durability. The aim of the present research has been comparing the impact of 2 types of modifier (which are, the propylene modifier [PP] and the styrene-butadiene-styrene [SBS]) on efficiency of the porous asphalt mixture. The evaluation of PAM has been based upon the asphalt flow drains down, air voids, and abrasion resistance at the step of the mix design. The performance of the mix has been investigated by permeability, rutting and moisture susceptibility. The test results have emphasized the significance of the use of the modifier in the minimization of abrasion loss, reduction of the rutting and enhancement of the PAC mix durability. The porous asphalt mixes that were prepared with 5% SBS modifier have been the most effective at increase of abrasion resistance and reduction of the rutting; and PP did not have any effects on the strength of the mixture.